Accuracy Comparison between Frameless Biopsy and Frame-Based Biopsy: A Retrospective Study of a Case Series - Braga, Henrique Moura; Dellaretti, Marcos Antônio; Faria, Marcello Penholate; Almeida, Júlio Cezar de; Nascimento, Leyzeane Marques do (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Objective To compare the efficacy and safety of frameless and frame-based techniques for biopsies of intracranial lesions in an exclusive assistance service at a public health center in Brazil (SUS).Method A review of 65 medical records of patients with brain lesions who underwent a frame-based or frameless biopsy from September 2017 to July 2019 was performed.Results Among the 65 patients who underwent biopsy, 42 were male, and 23 were female. The mean age was 53.1 years. Most patients (49; 75.4%) presented hemispheric lesions, and, of these, 27 were in the frontal lobe (41,5%). The diagnostic rate was 78.5% (51 of 65 patients), and glial neoplasia was the most common diagnosis. In addition to glial neoplasia, a wide range of pathologies were diagnosed, such as toxoplasmosis, metastasis, lymphoma, inflammatory lesions, and abscesses. Among the 14 patients (21.5%) with inconclusive results, 8 had gliosis without neoplasia (12.3%), 4 had necrosis (6.1%), and 2 had insufficient samples (3%).The morbidity rate was 9.2%, with 4 cases of hemorrhage, 1 case of infection, and 1 case of worsening of neurological deficits. The mortality rate was 6.1% and occurred in all cases with hemorrhage.There were no significant differences in the diagnosis or complication (morbidity and mortality) rates between the frame-based and frameless groups.Conclusion The frame-based and frameless techniques for stereotactic biopsy present similar efficacy and safety.
Keywords: neurosurgery; biopsy; frameless; frame-based; intracranial; lesions